1981
DOI: 10.1136/adc.56.7.509
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-responsive and nephrotic syndrome and allergy: clinical studies.

Abstract: MMARY Eighty-four children with steroid-responsive nephrotic syndrome who had been shown to have, or were believed to have, minimal change histology were investigated to study the relationship between steroid-responsive nephrotic syndrome and allergy. They were found to have a greater incidence of the standard atopic disorders-asthma, eczema, recurrent urticaria, and hay fever. Their 1st-degree relatives had an increased incidence of these atopic disorders too. A nasal discharge was a frequent precursor or an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 16 publications
1
53
0
Order By: Relevance
“…Development of nephrotic syndrome may also follow allergic reactions in some cases (274). In atopy, Th2-mediated inflammation plays a central role.…”
Section: H Cytokines and Chemokinesmentioning
confidence: 99%
“…Development of nephrotic syndrome may also follow allergic reactions in some cases (274). In atopy, Th2-mediated inflammation plays a central role.…”
Section: H Cytokines and Chemokinesmentioning
confidence: 99%
“…Experimental data suggest that proteinuria in SSNS is mediated by a circulating factor(s) produced either by activated peripheral blood mononuclear cells (PBMC) or T lymphocytes [8][9][10][11]. Further evidence of an immune pathogenesis of SSNS arises from the clinical response to immunosuppressive treatment, and the increased incidence of atopy in affected children [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have associated INS with allergy risk of clinical and immunological features (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the 1950s through the 1970s, few anecdotal reports described patients who developed INS after allergic reactions to inhaled allergens, vaccinations, food, or insect stings (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Numerous studies have associated INS with allergy risk of clinical and immunological features (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the 1950s through the 1970s, few anecdotal reports described patients who developed INS after allergic reactions to inhaled allergens, vaccinations, food, or insect stings (2)(3)(4)(5). Since 1970, several case-control studies revealed that elevated serum IgE and atopic diathesis were more common in children with INS than non-INS controls (9,(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation